2020
DOI: 10.3390/ijms21051838
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Epigenetics: Non-Coding RNAs as a Novel Layer of Complexity

Abstract: Mitochondria are organelles responsible for several functions involved in cellular balance, including energy generation and apoptosis. For decades now, it has been well-known that mitochondria have their own genetic material (mitochondrial DNA), which is different from nuclear DNA in many ways. More recently, studies indicated that, much like nuclear DNA, mitochondrial DNA is regulated by epigenetic factors, particularly DNA methylation and non-coding RNAs (ncRNAs). This field is now called mitoepigenetics. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 99 publications
2
45
0
Order By: Relevance
“…Stemness could potentially be included to the list, as (cancer) stem cell mitochondrial metabolism most often differs from that of differentiated (cancer) cells [ 66 ]. While mtDNA encodes only 13 mitochondrial proteins in addition to 22 transfer RNAs and 2 ribosomal RNAs, SNPs, mutations, deletions and/or epigenetic changes (methylation, non-coding RNAs) could convey these traits long-term [ 67 ]. Conversely, gain of function mutations could fade away depending on the half-life of specific mitochondrial components that would directly or indirectly depend on the nuclear DNA expression of donor cells.…”
Section: Conclusion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Stemness could potentially be included to the list, as (cancer) stem cell mitochondrial metabolism most often differs from that of differentiated (cancer) cells [ 66 ]. While mtDNA encodes only 13 mitochondrial proteins in addition to 22 transfer RNAs and 2 ribosomal RNAs, SNPs, mutations, deletions and/or epigenetic changes (methylation, non-coding RNAs) could convey these traits long-term [ 67 ]. Conversely, gain of function mutations could fade away depending on the half-life of specific mitochondrial components that would directly or indirectly depend on the nuclear DNA expression of donor cells.…”
Section: Conclusion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Although the characterization of the mitoRNA landscape in mouse male germ cells, gametes, and zygotes opens the door to novel mechanisms of regulation in mitochondria, much effort is required to unravel the biological functions of these RNAs in germ cell functions and how these molecules may coordinate signalling pathways between nucleus and mitochondria [ 39 ].…”
Section: Mitochondria: a Central Role In Sperm Physiologymentioning
confidence: 99%
“…Instead, the level of 5hmC in the mtDNA of AD patients did not change notwithstanding a previous study reported a 5hmC level reduction in aging-associated mtDNA [364]. The discrepancy between Blanch and Dzitoyeva [363,364] studies could be due to the differences between species (humans vs. mice, respectively) and/or the methods used. Dysregulation of mtDNA epigenetic mechanisms could partially explain mitochondrial dysfunction, a recurrent feature of AD [362].…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 71%
“…However, little is known about the mechanisms underlying mitoepigenetics. Blanch et al [363] found a global reduction of 5mC in mtDNA. Analysis of specific loci showed that the levels of 5mC in MT-ND1, a mitochondrial gene encoding a protein of the complex I of the respiratory chain, were lower in the entorhinal cortex of AD patients compared with that in age matched controls.…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 97%